Menelusuri Penyebab Ketidakaktifan BUMDesa di Provinsi Jambi - Lubis, Tona Aurora; Firmansyah, Firmansyah; Ningsih, Maryati (Universitas Batanghari Jambi, 2024)
The purpose of this study is to formulate a model of the inactive BUMDesa factors in Jambi Province. This type of research is a type of qualitative research research with a phenomenological type. This qualitative research analysis will be assisted by using the Nvivo qualitative research software. Based on the research results, it can be concluded that the main factors causing the inactivity of BUMDes in Jambi province can be divided into 3, these are: BUMDes management factors, village officials and the community.